Bicuspid aortic valve with right‐sided aortic arch aneurysm and Kommerell's diverticulum. Issue 9 (17th May 2019) - Zhao, Cuiting; Sun, Yang; Wang, Yonghuai; Li, Guangyuan; Meng, Pingping; Liu, Shuang; Yang, Jun; Ma, Chunyan
Abstract: Bicuspid aortic valve (BAV) is a common congenital cardiac malformation, frequently combined with ascending aorta dilation. However, isolated abnormalities of the aortic arch are less frequent in BAV patients. Here, we present a rare case of BAV combined with right‐sided aortic arch aneurysm, aberrant left subclavian artery, and Kommerell's diverticulum, diagnosed by echocardiography and computed tomography angiography. The patient was followed‐up regularly because of the life‐threatening risks of aortic arch aneurysms.